Systematic review and meta-analysis of the use of lean methods and tools in healthcare services: an alternative to improve care during the pandemic (Revista do LabDGE - UFF, 2023)
Background: Lean approach has become a trend due to its credibility achieved in several sectors, including Health services having target at the care and security of patients. This paper aims to map how Lean tools are being used in healthcare and what are their results, including those related to humanization.Methods: A Systematic Literature Review was performed according to the following steps: search for articles approaching the Lean Healthcare theme published in English between 2014 and 2020, selected on the databases of Web of Science, Scopus and Compendex (no other articles were introduced on the literature review), followed by discarding duplicates. The records were screening focusing in the section of articles reporting cases of lean healthcare adopting. No articles were excluded after the screening, which resulted in 48 articles that were deeper analysed through both qualitative and quantitative analyses.Results: Value Stream Mapping (VSM), 5S and Kaizen were the most used Lean tools in related study, with 24, 14 and 13 occurrences. The simulation and the “5 Whys” were Lean tools less used, with 3 and 2 occurrences. The main benefits found with the use of such tools were a reduction in the service time and an increase in patient satisfaction. The influence of teams and doctors behavior was identified as barrier to Lean implementation.Conclusions: The word "human" was discovered to be the most used word to describe Lean works in healthcare, that was not related in earlier reviews. There was also an increase in the number of Brazilian publications on subject, compared to previous period, in which the United States led on the number of publications. Throughout the study, two related cases added an annual savings of US $ 444,911, with the implementation of Lean Healthcare. The Lean approach has been applied in some health services to reduce the time of attendance and increase patient satisfaction. These results are indicative for expanding its application in the context of pandemics such as COVID-19.